"Buy Two Get One" - Transforming Dharma into commodity in the Touristic Buddhist Temples of North-eastern, Thailand. Issue 3 (2018) - Prabnok, Puttharak; Chamaratana, Thanapauge; Sirisuwilai, Watcharapon; Jirasatthumb, Norachit; Klaydesh, Panya
No abstract available